Analysis of Students' Understanding and Motivation of Volleyball Extracurricular Activities at SMK Sariwangi Tasikmalaya - Prabowo, Agung; Nurnisaa Binti Abdullah Suhaimi; Cahyandari, Rini (Corespub, 2024)
This research aims to evaluate the understanding and motivation of Tasikmalaya 1 Public High School students towards the extracurricular sport of volleyball. The research method used is quantitative descriptive using a Likert scale. The research results show that some students still have a limited understanding of volleyball, even though the majority like this extracurricular activity. Lack of motivation in playing volleyball is caused by limited facilities and limited practice time. Characteristics of volleyball extracurricular participants include a high level of sportsmanship, while the teenage phase marks a significant phase in the participant's development. This research highlights the importance of developing intrinsic motivation in students to increase participation in extracurricular activities and offers insight into how volleyball extracurriculars can be an effective tool in student character formation and self-development.